2020 IEEE 5th International Conference on Computing Communication and Automation (ICCCA) 2020
DOI: 10.1109/iccca49541.2020.9250748
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Different Regression Models on Predicting the Spread of Covid-19 in India

Abstract: According to the World Health Organization (WHO) Situation Reports of Corona Virus Disease(Covid-19), as on 15 th May 2020, India has 81,970 totals confirmed cases, 2649 total deaths and is still within the limit of community transmission phase. In this study, we analyze the spread of the disease and the fatalities caused up to 15 th May 2020, as per the data obtained. A granular computing based regression model, namely Granular Box Regression is used along with Linear Regression for comparative analysis to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In [59] Chakraborty et al proposed to use Linear Regression, Polynomial Regression and a granular computing based regression model, the Granular Box Regression (GBR), to predict the daily increase of new COVID-19 cases in India. GBR finds the relationship between independent variables and a dependent variable by using multidimensional boxes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [59] Chakraborty et al proposed to use Linear Regression, Polynomial Regression and a granular computing based regression model, the Granular Box Regression (GBR), to predict the daily increase of new COVID-19 cases in India. GBR finds the relationship between independent variables and a dependent variable by using multidimensional boxes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same way, Chakraborty et al [29] compared the performance of the linear regression model, granular box regression, and the polynomial regression model in predicting the spread of COVID-19 in India. The authors reported that the polynomial regression model outperformed the two other models.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way Chakraborty et al, 2020 [29] compared the performance between Linear Regression model, Granular Box Regression (GBR) and the Polynomial Regression model in predicting the spread of COVID-19 in India. The authors reported that the Polynomial regression model surpassed the two other models.…”
Section: Introductionmentioning
confidence: 99%